Equity: Not only for idealists - Haddad, Lawrence James (Wiley, 2015)
Growing disparities in development outcomes are storing up trouble for current and future generations. In addition to the moral issues raised and the intrinsic welfare effects for those experiencing relative deprivation, this article argues that recent research supports a stronger public‐policy focus on equity. Increasing inequity blunts both growth and the ability of growth to translate into human‐development outcomes, and puts institutions, social cohesion and the productivity of future generations at risk. The article highlights new micro evidence suggesting that a focus on the most marginal might well lead to higher benefit:cost ratios, and outlines the choices that need to be made to generate a more equity‐focused policy agenda.